Wawasan Moderasi Beragama Dalam Pengembangan Desain Pembelajaran Pendidikan Agama Islam - YORDAN NAFA; Moh. Sutomo; Mashudi Mashudi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This article discusses about the urgency of religious moderation insight in the development of Islamic Religious Education design. Religious moderation is one of the basic concepts that are important for students to understand in order to raise up the value of tolerance. The Islamic Religious Education teachers have the important role in designing learning, so that the values ​​of religious moderation can be conveyed and internalized properly to students. The purpose of this research is finding out and explaining the insight of religious moderation in the development of Islamic Religious Education learning design. This study uses a descriptive qualitative approach by using a literature study method. The author acts as the main instrument in planning, collecting data, and interpreting data. Based on data sources from various related literacies, it was found that understanding and internalizing religious moderation is important for students to raise up national commitment, tolerance, anti-radicalism and violence, as well as an accommodative attitude towards local wisdom. Islamic Religious Education Learning that is designed creatively and comprehensively can increase the success of learning, so that the insight of religious moderation can be understood and internalized properly to students.